Toekomstbestendig renoveren - Henk Brinksma (A+BE: Architecture and the Built Environment, 2017)
Homes are renovated a number of times during their lifespan. Although we can regard each of these renovations as new, it is more prudent to implement a future-proof solution to renovation. Current renovation practice focuses on renovating to meet current demand. Many of the renovations are still extremely labour intensive and occur on site. This results in solutions to ensure that the house once again meets the required standards in the short term. These standards will continue to change in the future, however. Our homes will continually require renovation. The question is how we can arrive at solutions that do not impede these future renovations, and implement future-proof solutions that can be applied to a large percentage of housing stock.